Urine biomarker could be a useful tool for differential diagnosis of a lower urinary tract dysfunction - Wan-Ru Yu; Yuan-Hong Jiang; Jia-Fong Jhang; Hann-Chorng Kuo (Tzu Chi Medical Journal)
A precision diagnosis of lower urinary tract dysfunctions (LUTD) such as bladder outlet obstruction, detrusor overactivity (DO), interstitial cystitis/bladder pain syndrome (IC/BPS), dysfunctional voiding (DV), or detrusor underactivity (DU) needs invasive videourodynamic study. Exploring non-invasive tools to help screening LUTD is necessary for clinicians in their daily practice. This article reviews recently clinical studies of using urinary inflammatory proteins and oxidative stress biomarkers in the identification of specific LUTD among men and women with lower urinary tract symptoms (LUTS). Some important findings have been reported: (1) Using urine chemokines CXCL-1 and interleukin-8 (IL-8), we may discriminate overactive bladder (OAB) symptoms in women between DO and urinary tract infection. (2) Urinary levels of oxidative stress biomarkers such as 8-hydroxydeoxyguanosine (8-OHdG) and 8-isoprostane have a potential being used as a tool to identify women with mixed DO and stress urinary incontinence. (3) Urine levels of total antioxidant capacity (TAC), and prostaglandin E2 (PGE2) are positively correlated with voiding detrusor pressure in patients with DU. (4) Urine levels of brain-derived neurotrophic factor (BDNF) and PGE2 were significantly higher in the DU patients with detrusor function recovery. (5) Women with DV had higher urinary levels of tumor necrosis factor-alpha (TNF-α) and 8-OHdG, and urinary IL-2 level was significantly lower. (6) Urine level of 8-isoprostane was higher in the patients with idiopathic DO and neurogenic DO. (7) Higher urine cytokine levels of monocyte chemoattractant protein-1 (MCP-1), regulated on activation, normal T-cell expressed and secreted (RANTES), CXCL-10, IL-7, and eotaxin-1 in patients with IC/BPS than controls. (8) The urine levels of IL-8, CXCL-10, BDNF, IL-6, and RANTES were significantly higher in patients with Hunner's IC than non-Hunner's IC. (9) Male patients with IC/BPS had a significantly higher level of eotaxin, MCP-1, TNF-α, 8-OHdG, and TAC. Combining a higher eotaxin and a higher TNF-α can provide a satisfactory diagnostic value in discriminating IC/BPS from other LUTD in men. These studies provide evidence that measurement of cluster of urine biomarkers could be used as a diagnostic tool to differentiate different LUTD in patients with similar LUTS.